La santé en contexte francophone minoritaire au Canada : 20 ans de recherche: Introduction - Bouchard, Louise; Savard, Jacinthe; Dumond, Morgan (Minorités linguistiques et société, 2024)

État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Perception du contexte linguistique et culturel minoritaire sur le vécu de la grossesse - Lacaze-Masmonteil, Thierry; Leis, Anne; Lauriol, Emmanuelle; Normandeau, Joane; Moreau, Denise; Bouchard, Louise; Vaillancourt, Cathy (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Dans une perspective de santé publique, le suivi de grossesse et la période périnatale exigent une communication de qualité et des services de santé qui tiennent compte du contexte dans lequel ces femmes évoluent. Or, des défis d’accès aux services de santé en français en situation minoritaire au Canada ont été documentés. Cette étude pilote a pour objectif de mieux cerner les perceptions et le vécu de femmes enceintes francophones vivant au Canada dans un contexte linguistique minoritaire Méthodes Étant donné la nature exploratoire du questionnement, une étude descriptive alliant des méthodes quantitative et qualitative a été mis en œuvre en Alberta et au Nouveau-Brunswick, dont les populations sont de 2 % et 33 % francophones, respectivement. Deux entrevues semi-structurées et une série de questionnaires ont été administrées auprès de 21 femmes enceintes au début du troisième trimestre de grossesse et à six semaines après la naissance. Une analyse descriptive des questionnaires a permis de dresser le profil et les caractéristiques des participantes, et les entrevues qualitatives, transcrites, codées et analysées de façon inductive par quatre lecteurs indépendants, ont fait ressortir plusieurs thèmes Clés en rapport avec leurs expériences. Résultats La plupart des participantes se sont dites bilingues et la langue ne semble pas avoir été un enjeu majeur dans l’évaluation des services de santé reçus sauf en situation de stress et lors de certaines périodes critiques de la grossesse et de l’accouchement. Par contre, près d’un tiers des participants se disent insatisfaites des services de santé reçus et l’insuffisance de suivi en français est mentionnée comme un des facteurs contribuant à cette insatisfaction. Conclusion Les services de santé sont préférés dans la langue maternelle des femmes mais reçus dans la langue de la majorité la plupart du temps. En situation de stress ou de complication de grossesse, les témoignages des participantes semblent indiquer que la communication en français est un facteur essentiel d’un suivi de grossesse de qualité. Une étude comparative permettrait de mieux distinguer l’impact spécifique de la langue dans l’expérience vécue des femmes enceintes.

The health impact of living in a nursing home with a predominantly different spoken language: Lettor to the Editor - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes. Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services. French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones. However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored. We conducted a population-based retrospective cohort study to assess the impact of language discordance on hospitalizations, emergency department (ED) visits, and mortality in a cohort of 122,416 incident admissions to nursing homes in Ontario between 2010 and 2016.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.